Values at work: the vision propagandist center-west region of Rio Grande do Sul - Lopes, Luis Felipe Dias; Freitas, Andrea Karla Breunig de; Tatsch, Marcelo Pastoriza; Madruga, Lucia Rejane da Rosa Gama; Imhoff, Olair (Revista de Administração da UFSM, 2014)
The value can be defined as principles or beliefs about desirable goals or rewards, hierarchically organized, that people seek through their work and guide their evaluations of the results and the work context, as well as their behavior in work and make a choice of work. The development of studies using scales of values is still little, but on work values exists Scale the Work Values (SWV) that has been used in scientific work. A group of 40 propagandists of the center-west region of the state of Rio Grande do Sul answered this survey. These data were subjected to a reliability analysis, descriptive and correlational. The results indicated that the factors could be improved with regard to reliability, to the exclusion of any item, but according to the authors, all factors are within the acceptable tolerance limit, that is, all items are important in the formation factors and their opinion makers about the Work Relative Value (WRV).